Immunotropic effects of so-called slag metabolites (creatinine, urea, uric acid and bilirubin) at rats - Popovych, Igor; Gozhenko, Anatoliy; Kuchma, Igor; Zukow, Walery; Bilas, Volodymyra; Koval’chuk, Galyna; Ivasivka, Anzhela (Journal of Education, Health and Sport, 2020)
Background. The study of the effect of end products of protein and nucleic acid metabolism on the immune system is of interest not only theoretical but also practical in line with the problems of urotoxins and hemodialysis. In previous studies, we found significant links between uricemia and uricosuria, on the one hand, and immune parameters, on the other hand. In this study, the spectrum of nitrogenous metabolites was expanded due to creatinine, urea and bilirubin. Material and methods. Experiment was performed on 60 healthy female Wistar rats. The plasma level and urinary excretion of the nitrogenous metabolites were determined. Immune status was assessed by thymocytogram, splenocytogram, blood leukocytogram and immunocytogram, as well as phagocytosis of blood neutrophils and monocytes. Results. Both negative and positive metabolic-immune correlations were revealed. Calculation of multiple correlation coefficients between individual metabolite parameters and constellations of immune parameters revealed the maximum immunotropic effect of uricosuria (R=0,637). This is followed by excretion of urea (R=0,617) and creatinine (R=0,606), bilirubinemia (R=0,589), creatinineemia (R=0,567), uricemia (R=0,566) and plasma urea level (R=0,500). The canonical correlation between the constellation of nitrogenous metabolites, on the one hand, and the parameters of immunity, on the other hand, was very strong: R=0,921; χ2(154)=282; p<10-6. Conclusion. Nitrogen metabolites exhibit significant immunotropic activity, both suppressor and enhancing.